Multipronged infection control strategy to achieve zero nosocomial coronavirus disease 2019 (COVID-19) cases among Hong Kong healthcare workers in the first 300 days of the pandemic. (19th March 2022) - Cheng, Vincent Chi-Chung; Wong, Shuk-Ching; Tong, Danny Wah-Kun; Chuang, Vivien Wai-Man; Chen, Jonathan Hon-Kwan; Lee, Larry Lap-Yip; To, Kelvin Kai-Wang; Hung, Ivan Fan-Ngai; Ho, Pak-Leung; Yeung, Deacons Tai-Kong; Chung, Kin-Lai; Yuen, Kwok-Yung
Abstract: Background: Nosocomial outbreaks leading to healthcare worker (HCW) infection and death have been increasingly reported during the coronavirus disease 2019 (COVID-19) pandemic. Objective: We implemented a strategy to reduce nosocomial acquisition. Methods: We summarized our experience in implementing a multipronged infection control strategy in the first 300 days (December 31, 2019, to October 25, 2020) of the COVID-19 pandemic under the governance of Hospital Authority in Hong Kong. Results: Of 5, 296 COVID-19 patients, 4, 808 (90.8%) were diagnosed in the first pandemic wave (142 cases), second wave (896 cases), and third wave (3, 770 cases) in Hong Kong. With the exception of 1 patient who died before admission, all COVID-19 patients were admitted to the public healthcare system for a total of 78, 834 COVID-19 patient days. The median length of stay was 13 days (range, 1–128). Of 81, 955 HCWs, 38 HCWs (0.05%; 2 doctors and 11 nurses and 25 nonprofessional staff) acquired COVID-19. With the exception of 5 of 38 HCWs (13.2%) infected by HCW-to-HCW transmission in the nonclinical settings, no HCW had documented transmission from COVID-19 patients in the hospitals. The incidence of COVID-19 among HCWs was significantly lower than that of our general population (0.46 per 1, 000 HCWs vs 0.71 per 1, 000 population; P = .008). The incidence of COVID-19 among professional staff was significantly lower than that of nonprofessional staff (0.30 vs 0.66 per 1, 000 full-time equivalent; P = .022). Conclusions: A hospital-based approach spared our healthcare service from being overloaded. With our multipronged infection control strategy, no nosocomial COVID-19 in was identified among HCWs in the first 300 days of the COVID-19 pandemic in Hong Kong.